2021
DOI: 10.3389/fmicb.2021.666097
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of ExoY Activity in Pseudomonas aeruginosa Reference Panel Strains and Impact on Cytotoxicity in Epithelial Cells

Abstract: ExoY is among the effectors that are injected by the type III secretion system (T3SS) of Pseudomonas aeruginosa into host cells. Inside eukaryotic cells, ExoY interacts with F-actin, which stimulates its potent nucleotidyl cyclase activity to produce cyclic nucleotide monophosphates (cNMPs). ExoY has broad substrate specificity with GTP as a preferential substrate in vitro. How ExoY contributes to the virulence of P. aeruginosa remains largely unknown. Here, we examined the prevalence of active ExoY among stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…There are four characterized effectors in P. aeruginosa: ExoS, ExoT, ExoU and ExoY, with ExoS and ExoU generally being mutually exclusive [7]. While a majority of isolated strains encode the nucleotidyl cyclase ExoY, its effect on various types of host cells has only recently been explored, and it may play a role in limiting cytotoxicity elicited by other effectors [8]. ExoY can contribute to virulence in corneal cells [9], but appears dispensable in some in vivo models despite various in vitro phenotypes [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…There are four characterized effectors in P. aeruginosa: ExoS, ExoT, ExoU and ExoY, with ExoS and ExoU generally being mutually exclusive [7]. While a majority of isolated strains encode the nucleotidyl cyclase ExoY, its effect on various types of host cells has only recently been explored, and it may play a role in limiting cytotoxicity elicited by other effectors [8]. ExoY can contribute to virulence in corneal cells [9], but appears dispensable in some in vivo models despite various in vitro phenotypes [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The ExoY protein sequence encoded by different P. aeruginosa strains varies. Sequence variations can be without consequences on enzymatic activity, modulate it, or even nearly abolish it, as in the case of the ExoY sequences identified in highly virulent PA14 strains [ 94 , 95 ]. These variations, which may be a consequence of long-term evolution or short-term adaptation of P. aeruginosa strains, complicate the identification of the role of Pa -ExoY exotoxins.…”
Section: Actin-activated Bacterial Toxinsmentioning
confidence: 99%
“…These variations, which may be a consequence of long-term evolution or short-term adaptation of P. aeruginosa strains, complicate the identification of the role of Pa -ExoY exotoxins. In a recent study, we examined the prevalence of ExoY activity in the largely diverse P. aeruginosa isolates of the international P. aeruginosa reference panel [ 95 ]. We found that ExoY GC activity is widespread among P. aeruginosa isolates, including those originating from cystic fibrosis patients, and that activity levels vary between strains (when measured in supernatants of bacterial cultures stimulated to secrete T3SS effectors by Ca++ chelation).…”
Section: Actin-activated Bacterial Toxinsmentioning
confidence: 99%
See 1 more Smart Citation
“…In in vivo settings, bacteria must naturally come into contact with human cells to induce exoY expression. The in vivo environment may yield lower exoY expression than in vitro , where there are no barriers to prevent exoY expression ( Silistre et al, 2021 ).…”
Section: Pao1 and Pa14 Virulence Determinant Differencesmentioning
confidence: 99%